Conditioned comfort: A multi-scalar analysis of residential heat adaptation in the tropical city-state of Singapore - Sarah Hian May Chan; Joshua Dao-Wei Sim; Natalia Borzino; Yunjing Li; Khant Min Naing; Pearl Min Sze Tan; Yi Xuan Tay; Flora Yuting Du; Samuel Chong Wei Chng; Jason Kai Wei Lee; Kai Zheng; Harvey Neo (Urban Climate, 2026)

Private cooling, urban heat, and the limits of collective climate action in tropical cities - Natalia Borzino; Samuel Chng; Sarah Hian May Chan; Khant Min Naing; Yi Xuan Tay; Harvey Neo (Sustainable Cities and Society, 2026)

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Spatio-temporal modeling of PM2.5 exposure in California's San Joaquin Valley using a community sensor network - Kate DeMarsh; Alec M. Chan-Golston; Zeyi Moo; Peizhi Hao; Yaying Wang; Kimberly Valle; Sandie Ha; Asa Bradman; Tim Tyner; Samuel Markolf; Xuan Zhang (Journal of Environmental Management, 2026)

Covariations of coral, macroalgal, macroinvertebrate and fish communities in an urbanised tropical reef environment - Stacia Loong; Daisuke Taira; Y. K. Samuel Chan; W. W. Rochelle Chan; Jenny Fong; Valerie Kwan; Jeffrey K. Y. Low; C. S. Lionel Ng; Shu Qin Sam; Charles Zhiming Tan; Karenne P. P. Tun; Zhi Ting Yip; et al. (Coral Reefs, 2026)

Towards a whole process engineering approach for enhancing physical and psychological health in underground environments: A systematic review - Isabelle Y.S. Chan; Samuel Twum-Ampofo; Benjamin K. Ababio; Frank Ato Ghansah; Shimeng Li (Tunnelling and Underground Space Technology, 2025)

Holocene coral assemblages reveal similarities to living communities in Singapore's urban reef environment - Y.K. Samuel Chan; Ambert C.F. Ang; Min Choo; Ren Min Oh; Kyle M. Morgan; Peter A. Todd; Michael J. O'Leary; Danwei Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Higher bisphenol analogues exposure levels in e-waste workers and their associations with DNA oxidative damage in Hong Kong - Gengze Liao; Xueqiong Weng; Feng Wang; Yanny Hoi Kuen Yu; Samuel Yeung-shan Wong; Victoria H. Arrandale; Alan Hoi-shou Chan; Shaoyou Lu; Lap Ah Tse (Environmental Research, 2025)

What do women want to see in a personalized breast cancer risk report? A qualitative study of Asian women of two countries - Fatma Aldila; Fiona Ng FJ; Jessica Audrienna; Lynn Lim SJ; Shannon Tang; Sabrina Gabriel Tanu; Eric Aria Fernandez; Faustina Audrey Agatha; Marco Wijaya; Stevany Tiurma Br Sormin; Levana Sani; Astrid Irwanto; et al. (Journal of Community Genetics, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Polyhydroxyalkanoate production in a biofilm by mixed culture phototrophic bacteria - Tim Hülsen; Daniel Venturato; Clement Chan; Luigi Vandi; Bronwyn Laycock; Steven Pratt; Samuel Stegman; Mark van Loosdrecht; Damien J. Batstone (Journal of Cleaner Production, 2024)

Seq’ and ARMS shall find: DNA (meta)barcoding of Autonomous Reef Monitoring Structures across the tree of life uncovers hidden cryptobiome of tropical urban coral reefs - Yin Cheong Aden Ip; Jia Jin Marc Chang; Ren Min Oh; Zheng Bin Randolph Quek; Yong Kit Samuel Chan; Andrew G. Bauman; Danwei Huang (Molecular Ecology, 2023)
Coral reefs are among the richest marine ecosystems on Earth, but there remains much diversity hidden within cavities of complex reef structures awaiting discovery. While the abundance of corals and other macroinvertebrates are known to influence the diversity of other reef‐associated organisms, much remains unknown on the drivers of cryptobenthic diversity. A combination of standardized sampling with 12 units of the Autonomous Reef Monitoring Structure (ARMS) and high‐throughput sequencing was utilized to uncover reef cryptobiome diversity across the equatorial reefs in Singapore. DNA barcoding and metabarcoding of mitochondrial cytochrome c oxidase subunit I, nuclear 18S and bacterial 16S rRNA genes revealed the taxonomic composition of the reef cryptobiome, comprising 15,356 microbial ASVs from over 50 bacterial phyla, and 971 MOTUs across 15 metazoan and 19 non‐metazoan eukaryote phyla. Environmental factors across different sites were tested for relationships with ARMS diversity. Differences among reefs in diversity patterns of metazoans and other eukaryotes, but not microbial communities, were associated with biotic (coral cover) and abiotic (distance, temperature and sediment) environmental variables. In particular, ARMS deployed at reefs with higher coral cover had greater metazoan diversity and encrusting plate cover, with larger‐sized non‐coral invertebrates influencing spatial patterns among sites. Our study showed that DNA barcoding and metabarcoding of ARMS constitute a valuable tool for quantifying cryptobenthic diversity patterns and can provide critical information for the effective management of coral reef ecosystems.

Mechanical ventilation and indoor air quality in recently constructed U.S. homes in marine and cold-dry climates - Chrissi A. Antonopoulos; Samuel I. Rosenberg; Haoran Zhao; Iain S. Walker; William W. Delp; Wanyu Rengie Chan; Brett C. Singer (Building and Environment, 2023)

Predicting habitat suitability for Amynthas spp. in the United States: a retrospective analysis using citizen science data from iNaturalist - L. Tucker Serniak; Samuel S. Chan; Kate Lajtha (Biological Invasions, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Microbial diversity of sub-bottom sediment cores from a tropical reef system - Ren Min Oh; Zheng Bin Randolph Quek; Yong Kit Samuel Chan; Ambert Chiam Foong Ang; Michael J. O’Leary; Danwei Huang; Benjamin J. Wainwright (Coral Reefs, 2022)

Dosimetric evaluation of a patient-specific 3D-printed oral positioning stent for head-and-neck radiotherapy - Susannah Cleland; Philip Chan; Benjamin Chua; Scott B. Crowe; Jodi Dawes; Lizbeth Kenny; Charles Lin; Elise Obereigner; Samuel C. Peet; Jamie V. Trapp; Tania Poroa; Tanya Kairn (Physical and Engineering Sciences in Medicine, 2021)

Disabled-2: a positive regulator of the early differentiation of myoblasts - Na Shang; Juliana Tsz Yan Lee; Taida Huang; Chengdong Wang; Tin Lap Lee; Samuel C. Mok; Hui Zhao; Wood Yee Chan (Cell and Tissue Research, 2020)
Dab2 is an adaptor protein and a tumor suppressor. Our previous study has found that Dab2 was expressed in early differentiating skeletal muscles in mouse embryos. In this study, we determined the role of Dab2 in the skeletal muscle differentiation using C2C12 myoblasts in vitro and Xenopus laevis embryos in vivo. The expression of Dab2 was increased in C2C12 myoblasts during the formation of myotubes in vitro. Knockdown of Dab2 expression in C2C12 myoblasts resulted in a reduction of myotube formation, whereas the myotube formation was enhanced upon overexpression of Dab2 . Re-expression of Dab2 in C2C12 myoblasts with downregulated expression of Dab2 restored their capacity to form myotubes. Microarray profiling and subsequent network analyses on the 155 differentially expressed genes after Dab2 knockdown showed that Mef2c was an important myogenic transcription factor regulated by Dab2 through the p38 MAPK pathway. It was also involved in other pathways that are associated with muscular development and functions. In Xenopus embryos developed in vivo, XDab2 was expressed in the myotome of somites where various myogenic markers were also expressed. Knockdown of XDab2 expression with antisense morpholinos downregulated the expression of myogenic markers in somites. In conclusion, this study is the first to provide solid evidence to show that Dab2 is a positive regulator of the early myoblast differentiation.

Coral Reef Monitoring, Reef Assessment Technologies, and Ecosystem-Based Management - David O. Obura; Greta Aeby; Natchanon Amornthammarong; Ward Appeltans; Nicholas Bax; Joe Bishop; Russell E. Brainard; Samuel Chan; Pamela Fletcher; Timothy A. C. Gordon; Lew Gramer; Mishal Gudka; et al. (Frontiers in Marine Science, 2019)

A global review and meta-analysis of applications of the freshwater Fish Invasiveness Screening Kit - Lorenzo Vilizzi; Gordon H. Copp; Boris Adamovich; David Almeida; Joleen Chan; Phil I. Davison; Samuel Dembski; F. Güler Ekmekçi; Árpád Ferincz; Sandra C. Forneck; Jeffrey E. Hill; Jeong-Eun Kim; et al. (Reviews in Fish Biology and Fisheries, 2019)

Comparing patterns of taxonomic, functional and phylogenetic diversity in reef coral communities - Joy S. Y. Wong; Y. K. Samuel Chan; C. S. Lionel Ng; Karenne P. P. Tun; Emily S. Darling; Danwei Huang (Coral Reefs, 2018)

In vivo and in vitro sustained release of ranibizumab from a nanoporous thin-film device - Kevin D. Lance; Daniel A. Bernards; Natalie A. Ciaccio; Samuel D. Good; Thaís S. Mendes; Max Kudisch; Elliot Chan; Mynna Ishikiriyama; Robert B. Bhisitkul; Tejal A. Desai (Drug Delivery and Translational Research, 2016)

Preclinical Pharmacokinetics Study of R- and S-Enantiomers of the Histone Deacetylase Inhibitor, AR-42 (NSC 731438), in Rodents - Hao Cheng; Zhiliang Xie; William P. Jones; Xiaohui Tracey Wei; Zhongfa Liu; Dasheng Wang; Samuel K. Kulp; Jiang Wang; Christopher C. Coss; Ching-Shih Chen; Guido Marcucci; Ramiro Garzon; et al. (The AAPS Journal, 2016)

Core genome and plasmidome of the quorum-quenching bacterium Rhodococcus erythropolis - Anthony Kwasiborski; Samuel Mondy; Teik-Min Chong; Kok-Gan Chan; Amélie Beury-Cirou; Denis Faure (Genetica, 2015)

Narcissus tazetta lectin shows strong inhibitory effects against respiratory syncytial virus, influenza A (H1N1, H3N2, H5N1) and B viruses - Linda S. M. Ooi; Wing-Shan Ho; Karry L. K. Ngai; Li Tian; Paul K. S. Chan; Samuel S. M. Sun; Vincent E. C. Ooi (Journal of Biosciences, 2010)

In vitro myogenic and adipogenic differentiation model of genetically engineered bovine embryonic fibroblast cell lines - Jinlong Yin; Xun Jin; Samuel Beck; Dong Ho Kang; Zhongshan Hong; Zhehu Li; Yongcheng Jin; Qiankun Zhang; Yun-Jaie Choi; Sung-Chan Kim; Hyunggee Kim (Biotechnology Letters, 2010)

Serum zinc is decreased in Alzheimer’s disease and serum arsenic correlates positively with cognitive ability - Larry Baum; Iris Hiu Shuen Chan; Stanley Kwok-Kuen Cheung; William B. Goggins; Vincent Mok; Linda Lam; Vivian Leung; Elsie Hui; Chelsia Ng; Jean Woo; Helen Fung Kum Chiu; Benny Chung-Ying Zee; et al. (BioMetals, 2010)

Expression and subcellular targeting of human insulin-like growth factor binding protein-3 in transgenic tobacco plants - Stanley C. K. Cheung; Samuel S. M. Sun; Juliana C. N. Chan; Peter C. Y. Tong (Transgenic Research, 2009)

Headwater Riparian Microclimate Patterns under Alternative Forest Management Treatments - Jessica J. Rykken; Samuel S. Chan; Andrew R. Moldenke (Forest Science, 2007)
Management of headwater streams and their riparian zones has included the implementation of forested riparian buffers, which are intended to protect ecological processes (such as microclimate) and biota, but the appropriate widths for these buffers have been widely debated. We measured the magnitude and extent of microclimatic gradients associated with headwater streams in mature unmanaged forests, and determined whether these patterns were maintained in clearcut harvested units with and without a 30 m-wide riparian buffer on each side of the stream. We measured air temperature, soil temperature, and relative humidity between 1 and 70 m from the stream in five replicate blocks of three treatments each in western Oregon. Results indicated the strongest stream effect on air temperature and relative humidity to be within 10 m of the stream in all management treatments at 3:00 pm, and gradients were evident to 20 m in the forested treatment. The clearcut was significantly hotter (air and soil) and drier than either the riparian buffer or the forest treatments at 3:00 pm. The riparian buffer and forest had similar microclimates at all distances from the stream, suggesting that the 30-m buffer adequately protected the riparian microclimatic gradient. We hypothesize that the strong stream effect on microclimate in the riparian zone serves a critical role in mitigating the influence of microclimatic “edge effects” associated with the forest-clearcut edge. Biota dependent on cool, humid microclimates provided by riparian zones will benefit from the implementation of riparian buffers in harvest units.

Periphyton and Macroinvertebrate Assemblage Structure in Headwaters Bordered by Mature, Thinned, and Clearcut Douglas-Fir Stands - Robert J. Danehy; Samuel S. Chan; Gary T. Lester; Russell B. Langshaw; Ted R. Turner (Forest Science, 2007)
We examined the structure of periphyton and macroinvertebrate assemblages in 18 Oregon Coast Range perennial headwater streams bordered by mature (6), clearcut (5), and thinned (7) forest treatments. Summer base flow discharge ranged from 0.02 to1.98 l/s (mean − 0.5 l/s). Periphyton was almost entirely diatoms (72 species) and assemblage characteristics were most strongly influenced by substrate characteristics. Mature treatment sites had fewer species of diatoms and less biomass than other treatments. Diatom richness was highest at sites with higher unit area discharge. Diatom assemblages were dominated by a single species (Achnanthes lanceolata [Brébisson] Grunow), which composed more than 50% relative abundance of the assemblage at nine sites. Macroinvertebrate assemblages were rich, with 194 taxa collected across all sites and 42 taxa found at a single site. Macroinvertebrate assemblages differed across treatments with higher abundance, more Chironomidae taxa, and more biomass at the clearcut treatment sites. We observed no difference in functional feeding group percentage composition across treatments, with collector-gatherers and shredders composing at least 50% abundance at all treatments. We found little difference in either periphyton or macroinvertebrate assemblages between thinned and mature treatments.

Riparian Buffer and Density Management Influences on Microclimate of Young Headwater Forests of Western Oregon - Paul D. Anderson; David J. Larson; Samuel S. Chan (Forest Science, 2007)
Thinning of 30- to 70-year-old Douglas-fir (Pseudotsuga menziesii [Mirb.] Franco) stands is a common silvicultural activity on federal forest lands of the Pacific Northwest, United States. Empirical relationships among riparian functions, silvicultural treatments, and different riparian buffer widths are not well documented for small headwater streams. We investigated buffer width and density management effects on riparian microclimates of headwater streams in western Oregon. Spatial variations in stand density, canopy cover, and microclimate were measured along transects extending from stream center upslope into thinned stands, patch openings, or unthinned stands, with riparian buffers ranging from <5 m up to 150 m width. For treated stands, summer mean daily air and soil temperature maxima increased, and mean daily humidity minima decreased with distance from stream. Microclimate gradients were strongest within 10 m of stream center, a distinct area of stream influence within broader riparian areas. Thinning resulted in subtle changes in microclimate as mean air temperature maxima were 1 to 4°C higher than in unthinned stands. With buffers 15 m or greater width, daily maximum air temperature above stream center was less than 1°C greater, and daily minimum relative humidity was less than 5% lower than for unthinned stands. In contrast, air temperatures were significantly warmer within patch openings (+6 to +9°C), and within buffers adjacent to patch openings (+3°C) than within unthinned stands. Buffers of widths defined by the transition from riparian to upland vegetation or topographic slope breaks appear sufficient to mitigate the impacts of upslope thinning on the microclimate above headwater streams.

Wildlife Response to Thinning Young Forests in the Pacific Northwest - John P. Hayes; Samuel S. Chan; William H. Emmingham; John C. Tappeiner; Loren D. Kellogg; John D. Bailey (Journal of Forestry, 1997)

Scale-up of Adhesive Transdermal Drug Delivery Systems - Glenn A. Van Buskirk; Mario A. González; Vinod P. Shah; Scott Barnhardt; Colin Barrett; Stephen Berge; Gary Cleary; Keith Chan; Gordon Flynn; Thomas Foster; Robert Gale; Raymond Garrison; et al. (Pharmaceutical Research, 1997)